Comparing semi‐landmarking approaches for analyzing three‐dimensional cranial morphology. Issue 1 (23rd January 2021) - Rolfe, Sara; Davis, Christopher; Maga, A. Murat
Abstract: Objectives: Increased use of three‐dimensional (3D) imaging data has led to a need for methods capable of capturing rich shape descriptions. Semi‐landmarks have been demonstrated to increase shape information but placement in 3D can be time consuming, computationally expensive, or may introduce artifacts. This study implements and compares three strategies to more densely sample a 3D image surface. Materials and methods: Three dense sampling strategies: patch, patch‐thin‐plate spline (TPS), and pseudo‐landmark sampling, are implemented to analyze skulls from three species of great apes. To evaluate the shape information added by each strategy, the semi or pseudo‐landmarks are used to estimate a transform between an individual and the population average template. The average mean root squared error between the transformed mesh and the template is used to quantify the success of the transform. Results: The landmark sets generated by each method result in estimates of the template that on average were comparable or exceeded the accuracy of using manual landmarks alone. The patch method demonstrates the most sensitivity to noise and missing data, resulting in outliers with large deviations in the mean shape estimates. Patch‐TPS and pseudo‐landmarking provide more robust performance in the presence of noise and variability in the dataset. Conclusions: Each landmarking strategy was capable of producing shape estimations of the population average templates that were generally comparable to manual landmarks alone while greatly increasing the density of the shape information. This study highlights the potential trade‐offs between correspondence of the semi‐landmark points, consistent point spacing, sample coverage, repeatability, and computational time. Abstract : Triangular semi‐landmark patches placed on the gorilla skull population average model.